Assessing malleable social-psychological academic attitudes in early adolescence. (December 2018) - Pyne, Jaymes; Rozek, Christopher S.; Borman, Geoffrey D.
Abstract: Although it is important to accurately assess and promote student achievement, it is also critical to accurately assess and promote student social and emotional well-being and positive attitudes about school. Recent research has shown the promise of school-based interventions to improve certain student academic attitudes but has also raised concerns about a lack of reliable measures of these attitudes for early adolescents. We compiled the Malleable Social-Psychological Academic Attitudes (MSPAA) survey to measure school trust, social belonging, evaluation anxiety, self-complexity, locus of control, and identification with school. We adapted MSPAA measures to make them more appropriate for early adolescents in the school context, assessed the measurement properties of the MSPAA survey, and examined how student responses differed based on various demographic factors. We found that this brief survey reliably measured these constructs among early adolescents ( N = 2158). Additionally, differences by grade level, school context, gender, and racial group revealed insightful patterns of variation that have implications for social and psychological theory, as well as for practices in schools. We close by suggesting further study of this survey for use among education researchers and within schools. Highlights: The Malleable Social-Psychological Academic Attitudes survey assesses a novel group of attitudes of school-aged adolescents. Results show that these brief measures are reliable across school contexts, race, and gender. Student responses varied by grade, school context, gender, and race/ethnicity, informing theory and practices in schools.